(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: Longus colli provides stability to cervical spine during movements. In clinical practice, the clinicians teach exercises to longus colli to manage neck pain. The aim of this study was to investigate differences in thickness or anterior-posterior dimension (APD), shape ratio and contraction ratio of longus colli between subjects with neck pain and healthy controls. Materials and methods: A total of 12 subjects (6 with neck pain and 6 healthy controls) were recruited by predefined selection criteria. Ultrasound imaging of bilateral longus colli was conducted at the level C5-C6. Anterior-posterior dimension (APD) and lateral dimension (LD) were measured using Ultrasonography. Shape ratio (LD/APD) and contraction ratio (APD during contraction/APD during rest) were calculated. Mann-Whitney U test was used to compare the thickness of longus colli between healthy and neck pain subjects. Results and discussion: The results showed that the subjects with neck pain had smaller APD (Mean Rank=4.83, n=6) than healthy subjects (Mean Rank=8.17, n=6), U=16.00, z=-1.601 (corrected for ties), p=0.109, two tailed. Also, shape ratio showed higher values in neck pain subjects (Mean Rank=7.17, n=6) than normal subjects (Mean Rank=5.83, n=6), U=14.00, z=-0.641(corrected for ties) p=0.522, two tailed. In addition, contraction ratio was smaller in neck pain subjects (Mean Rank=4.83, n=6) than those healthy subjects (Mean Rank=8.17, n=6), U=8.00, z=- 1.601(corrected for ties) p=0.109, two tailed. Conclusion: There is a trend of reduced size of longus colli with the median of APD and smaller contraction ratio among patients with neck pain when compared to healthy controls. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13692 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 419-426